Mycobacteria and Fungi in Moisture-Damaged Building Materials - Torvinen, Eila (American Society for Microbiology, 2006)
In contrast to the growth of fungi, the growth of mycobacteria in moisture-damaged building materials has rarely been studied. Environmental mycobacteria were isolated from 23% of samples of moisture-damaged materials (n = 88). The occurrence of mycobacteria increased with increasing concentrations of fungi. Mycobacteria may contribute to indoor exposure and associated adverse health effects.